Perception of the virtual learning environment and social presence in Physiotherapy students during the COVID-19 pandemic - Ochoa, A. (2024)
Introduction: the aim of this study was to determine the association between the perception of the virtual learning environment and the social presence in Physiotherapy students during the COVID-19 pandemic. Material and method: the design was observational, cross-sectional and analytical. The perception of the virtual learning environment and social presence were measured through the Spanish version of the Distance Learning Education Environments Survey and Networked Minds Social Presence Measure questionnaires, respectively. The survey was sent to 223 students, but only 65 entered the research. Results: it was found that 76.9 % had regular internet quality, 84.6 % used a laptop as the main technological device for the study and 72.3 % indicated that the use of the device was exclusive. Regarding the virtual learning environment, the constructs «Active learning»(4.1 ± 0.6) and «Autonomy» (4.1 ± 0.6) obtained high scores; while, for social presence, the constructs «Co-presence» (5.4 ± 1.0) and «Perceived understanding of the message» (5.0 ± 0.9). In addition, it was found that «Teacher support» (r = 0.41, p < 0.001) and «Personal relevance» (r = 0.37, p = 0.002) were associated with social presence. Conclusion: an association was found between the perception of teacher support and personal relevance in the virtual learning environment and social presence in Physiotherapy students during the COVID-19 pandemic.